2020
DOI: 10.1111/jir.12772
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic syndrome and its components in people with intellectual disability: a meta‐analysis

Abstract: Background People with intellectual disability have an increased risk for cardiovascular diseases and associated premature mortality. Metabolic syndrome (MetS) and its components are highly predictive of cardiovascular diseases. The aim of this meta-analysis was to describe the pooled prevalence of MetS and its components in people with intellectual disability taking into account variations in demographic, clinical and treatment-related variables. Methods Pubmed, Embase and CINAHL were searched until 5 August … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 51 publications
0
12
1
Order By: Relevance
“…Surprisingly, our results show a markedly lower prevalence of hypertension among participants with intellectual disability. This finding is contrary to recent studies of hypertension in adults without CP, stating a prevalence of 31.1% in all adults (30), and 36.7% in adults with intellectual disability (31) and at this stage we have found no explanation for it. The high prevalence of high blood pressure measured at the visit might partly be due to the "white coat effect, " since the visit was a potentially stressful situation for the participant (19).…”
Section: Discussioncontrasting
confidence: 99%
“…Surprisingly, our results show a markedly lower prevalence of hypertension among participants with intellectual disability. This finding is contrary to recent studies of hypertension in adults without CP, stating a prevalence of 31.1% in all adults (30), and 36.7% in adults with intellectual disability (31) and at this stage we have found no explanation for it. The high prevalence of high blood pressure measured at the visit might partly be due to the "white coat effect, " since the visit was a potentially stressful situation for the participant (19).…”
Section: Discussioncontrasting
confidence: 99%
“…Age differences are determined by inclusion criteria and premature aging in association with ID [50]. A study by Vancamptort et al showed that people with intellectual disability have an increased risk of premature mortality [51]. Concerning marital status, the historical segregation of ID-afflicted people by sex has limited the scope of personal relationships during youth [52,53].…”
Section: Discussionmentioning
confidence: 99%
“…The high rates of AP use in individuals with IDD is quite concerning as the metabolic adverse effects exacerbate the already established inherent risk of metabolic comorbidities in these patient populations. A recent meta‐analysis revealed that ~52% of individuals with IDD are obese, while 22.4% meet the criteria for metabolic syndrome 14 . Moreover, the exceedingly high rates of cardiovascular and respiratory diseases in this population contributes to an almost two‐ to fourfold increased risk of premature mortality compared with the general population 14,15 …”
Section: Introductionmentioning
confidence: 99%
“…A recent meta‐analysis revealed that ~52% of individuals with IDD are obese, while 22.4% meet the criteria for metabolic syndrome 14 . Moreover, the exceedingly high rates of cardiovascular and respiratory diseases in this population contributes to an almost two‐ to fourfold increased risk of premature mortality compared with the general population 14,15 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation